The Artistic Structure And The Reflection Of Intellectual Consciousness In The In The Tahar Wattar’s Story Eshouhadaa Yaoudouna Hada El Usboua - .messili, tahar (El Omda in Linguistics and Discourse Analysis, 2026)
This study analyzes the artistic representation of post-independence Algerian reality in Eshouhadaa yaoudouna hada el usboua story it highlights how the narrative exposes systematic strategies of deception employed by forces opposing-nation building. The Analysis shows that the text aligns with the aesthetics of the modern story and conveys clear intellectual messages centred on national preservation and collective responsibility.